High prevalence of arthralgia among infants with Chikungunya disease during the 2019 outbreak in northern region of the state of Rio de Janeiro - Gomes, Patrícia Damião; Carvalho, Rayane Figueiredo Silva Moreira; Massini, Milena Moulin; Garzon, Rafael Hauaji; Schiavo, Pollianny Louzada; Fernandes, Regina Célia de Souza Campos; Louvain de Souza, Thaís (Frontiers in Pediatrics, 2022)
Introduction: In a low income setting with simultaneous presence of dengue virus, zika virus, and Chikungunya (CHIKV) in the same region difficulty of establishing a clinical diagnosis when the molecular test is not a possibility. Thus, it is important to identify signs and symptoms of Chikungunya that can be used to differentiate it from other arboviruses in children. Methods: This is a cross-sectional study, which was developed in Rio de Janeiro State, Brazil, with the analysis of pediatric medical records regarding arboviruses. Considering that the population had already been exposed to Dengue and Zika viruses and were experiencing the first notification of the CHIKV. The ethics committee approved this research, and all those legally responsible for the children signed the consent form. Results: In total, 159 children were seen of which 98 were suspected CHIKV cases, and 51 had their diagnosis confirmed with reagent IgM/IgG for CHIKV. The symptoms that the pediatric population with CHIKV presented most often were fever (90.2%), arthralgia (76.5%), and exanthema (62.7%) in both suspected and confirmed cases of Chikungunya. Thus, CHIKV in those children presents clinical profile similar to those found in other studies referring to adults. Additionally, only arthralgia and a high AST were related to the positivity of serology for Chikungunya. Conclusions: This study describe the signs and symptoms of CHIKV exhibited in the pediatric population with a mild and moderate presentation were similar to the findings in the adult during an epidemic experienced in a population vulnerable to CHIKV.